Solid-state NMR on the quadrupolar low-γ nucleus 25Mg: Application to glasses - Damasceno, Hugo Rodrigues (2023)
In the present work, the structure of magnesium alumino and aluminosilicate glasses were studied using several techniques of Solid State NMR. The study employed high magnetic field strengths and fast magic angle spinning to address the structural organization of the glasses. The utility of dipolar spin echo decay and static ultrawide line NMR (WURST) was tested on isotopically enriched 25Mg samples to extract information about the relevant interactions concerning the 25Mg nuclei. The results of the study were complemented by additional static and high-resolution 27Al and 29Si NMR techniques, which addressed the structural organization of the silicate and alumosilicate networks surrounding the magnesium ions. The 29Si MAS NMR spectroscopy was employed for the study, but due to limitations in the amount of material available and long spin-lattice relaxation times, reliable signal deconvolution was not obtained. The spectra were found to be consistent with previously published data, but the study found that the average isotropic chemical shifts and full widths at half maximum were found to be identical for the samples with and without 25Mg isotopic enrichment for MAS 226 glass, with stronger deviations for the other compositions. The 27Al MAS-NMR results suggest the presence of two distinct aluminum coordination environments in the samples and a small fraction of six-coordinated aluminum in the sample iso MAS 25. The findings were further validated by complementary techniques such as 27Al MQMAS NMR spectra and SATRAS-NMR. All these results form the basis of a comprehensive description of the local structure of magnesium silicate and alumosilicate glasses.